2017
DOI: 10.3847/1538-4357/aa79ab
|View full text |Cite
|
Sign up to set email alerts
|

The Splashback Radius of Halos from Particle Dynamics. II. Dependence on Mass, Accretion Rate, Redshift, and Cosmology

Abstract: The splashback radius R sp , the apocentric radius of particles on their first orbit after falling into a dark matter halo, has recently been suggested as a physically motivated halo boundary that separates accreting from orbiting material. Using the Sparta code presented in Paper I, we analyze the orbits of billions of particles in cosmological simulations of structure formation and measure R sp for a large sample of halos that span a mass range from dwarf galaxy to massive cluster halos, reach redshift 8, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
159
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(180 citation statements)
references
References 97 publications
18
159
0
Order By: Relevance
“…For v p >280 km s −1 subhalos, we find r sp =1.21 h −1 Mpc, while for the other two subhalo samples, we find r sp =1.47 h −1 Mpc. This ∼20% difference is consistent with that found in Diemer et al (2017).…”
Section: Effect Of Dynamical Frictionsupporting
confidence: 92%
See 2 more Smart Citations
“…For v p >280 km s −1 subhalos, we find r sp =1.21 h −1 Mpc, while for the other two subhalo samples, we find r sp =1.47 h −1 Mpc. This ∼20% difference is consistent with that found in Diemer et al (2017).…”
Section: Effect Of Dynamical Frictionsupporting
confidence: 92%
“…The sharp decline in the profile can be understood as resulting from an absence of particles orbiting beyond the radius of second turnaround. 54 In simulations, a phase-space caustic cleanly separates matter that is experiencing second turnaround from matter that is on first infall, leading to a very sharp steepening in the halo profile (DK14; Adhikari et al 2014;Diemer et al 2017). As measurements from individual halos are noisy, to detect this sharp steepening, one needs to "stack," or average, over a large number of halos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has hinted at this dependence of the backsplash population on the dynamical state of a cluster, by studying the splashback radius of clusters in different dynamical states, and accreting material at different rates. Numerous studies of the splashback feature in N -body simulations (Diemer & Kravtsov 2014;Diemer et al 2017) and in models of collapsing dark matter haloes (Adhikari et al 2014;More et al 2015) have found that the ratio between the splashback radius, Rsp, and R200 is smaller in rapidlyaccreting, unrelaxed clusters. Diemer & Kravtsov (2014) go on to explain that these clusters also typically form at later times, as indicated by Fig.…”
Section: Radial Backsplash Profilesmentioning
confidence: 99%
“…In N-body simulation, the location of this boundary corresponds to the first apocenter of the accreting dark matter particles, particularly referred to as the splashback radius. Because of its clear manifestation, the observational prospects and the theoretical understanding of the splashback feature as a unique signature of the CDM paradigm have attracted much attention (More et al 2015(More et al , 2016aShi 2016;Busch & White 2017;Diemer 2017;Diemer et al 2017;Adhikari et al 2018;Okumura et al 2018;Chang et al 2018;Contigiani et al 2019a,b).…”
Section: Introductionmentioning
confidence: 99%